The role of the HIV-1 gut reservoir in driving early cardiovascular events in people living with HIV - Kramer, Keri; Michael, Amanda; Quiñones, Guadalupe; Roa, Sebastian; Ribeiro, Susan P.; Lahiri, Cecile D.; Gavegnano, Christina (Frontiers in Drug Discovery, 2024)
People with HIV (PWH), even when well-controlled on antiretroviral therapy (ART), are at an increased risk for cardiovascular disease (CVD) and CVD events including sudden cardiac death and acute myocardial infarction (MI). While PWH may appear virally suppressed in peripheral blood, viral reservoirs persist in gut-associated lymphoid tissue (GALT) and have been shown to be associated with CVD-related morbidity and mortality. Effective treatments exist for CVD in HIV seronegative persons, but there is an unmet clinical need to address CVD in PWH. Novel therapies are needed to target the drivers of CVD in PWH. This literature review focuses on the role of GALT in HIV infection, inflammatory pathways in HIV-related CVD, and novel therapeutics with potential to address this problem.